(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Social media has emerged as a key element of modern society, allowing millions of people all over the world to interact, share information, and access content. This article presents a thorough analysis of the literature that is currently available regarding the benefits and drawbacks of social media. The study looks at social media’s benefits and drawbacks for both individuals and society as a whole. The paper discusses the advantages of social media, such as its ability to facilitate communication, connect people across geographic boundaries, and promote social change. It also examines the disadvantages of social media, including its potential to contribute to addiction, cyberbullying, and mental health issues. The paper concludes with suggestions for future research and provides recommendations for individuals, organizations, and policymakers to mitigate the negative effects of social media while harnessing its benefits. The study discussed about the evolution of social media. Overall, this review emphasizes the importance of understanding the complex and nuanced nature of social media’s impact and highlights the need for continued research and attention to this evolving phenomenon.